Hasil Seminar "Masa Lalu dan Masa Depan Bahasa Kei", Tual, 25-27 Oktober 1990 (Pusat Studi Maluku, Universitas Pattimura, 1990)
The past and future of the Kei language (or Evav) spoken in the Kei Islands, Kabupaten Maluku Tenggara, Maluku Province; papers of a seminar.